Características de liderazgo del administrador educativo de las Instituciones de Educación Superior en México - de la Garza Carranza, María Teresa; Cervantes Maldonado, Alfonso; Guzmán Soria, Eugenio; Ramos Estrada, Cecilia (Universidad de Costa Rica, 2017)
The presence of efficient administrators in educational organizations has been linked to organizational results and the achievement of goals since these officials are responsible for carrying out quality policies and for this they must resort to their leadership capacity. The present research article arises from the need to identify the main personal and interpersonal characteristics that take part in the leadership of educational administrators in public and private universities. The study was carried out based on a sample of managers of the COEPES (State Commission for the Planning of Higher Education) of the State of Guanajuato in Mexico during the years of 2015 to 2016. A model of structural equations was developed through Partial least squares technique, the results demonstrate that the model is reliable and valid. It also establishes the relationship between the variables personal and interpersonal capacities with the variable of leadership competence. It is concluded that personal and interpersonal skills influence leadership as suggested in the literature. This becomes even more important considering that a number of specialists in the field emphasize that leadership is a critical factor in enabling higher education institutions to achieve their goals. In addition, it is hoped that the results of this research will help managers in higher education institutions identify their own personal and interpersonal characteristics that influence their leadership skills and strengthen them, so that the strategic management of this type of institutions is improved.